Vascular Complications of Transradial Access for Cardiac Catheterization - Tanawan Riangwiwat (Radcliffe Medical Media, 2021)
Transradial access has been increasingly adopted for cardiac catheterization. It is crucial for operators to recognize potential vascular complications associated with radial artery access. Prevention, early detection, and prompt treatment of vascular complications are essential to prevent serious morbidities. This review aims to raise awareness of transradial access vascular complications. Radial artery spasm is treated with intra-arterial verapamil and/or nitroglycerine. Hemorrhagic complications, such as perforation, hematoma, arteriovenous fistula, and pseudoaneurysm, are treated with prolonged compression. Patent hemostasis and adequate anticoagulation are used to prevent radial artery occlusion. Hand ischemia is a rare complication not associated with abnormal results of the Allen or Barbeau test, and can be treated with intra-arterial verapamil, IV heparin, and IV diltiazem. Finally, an attentive monitoring protocol for the timely detection of vascular complications should be implemented in daily practice.